Getting Scrappy in the Classroom During COVID-19: Collaboration, Open Educational Resources, and Hands-on Learning for Humanities Students - Bassett, Elizabeth; Dean, Heather; Korda, Andrea; Leighton, Mary Elizabeth; Warne, Vanessa (KULA)

(untitled) (University of Victoria Libraries, 2022)
This teaching reflection, co-authored by two librarians and three instructors, offers a case study in collaborative assignment design and argues for the value of both collaboration as an instructional model and digital exhibitions as open educational resources. It explores how the transition to remote curating, learning, and teaching prompted by COVID-19 occasioned changes in how we curated exhibitions, on the one hand, and developed learning opportunities for students, on the other hand. Focused on a digital exhibition of nineteenth-century scrapbooks and the integration of scrapbooking—as a hands-on activity and a topic of scholarly inquiry—into three courses across two disciplines (English and art history), it also provides a model of how librarians and instructors might collaborate on assignment and coursedevelopment and scaffold such collaboration into assignment and course design. The reflection includes assignments and rubrics as well as examples of students’ work. It concludes with a series of recommendations for librarians and instructors who wish to collaborate.